PERAN RESTORATIVE JUSTICE DALAM PENGURANGAN OVERCROWDING DI LEMBAGA PEMASYARAKATAN KELAS I MAKASSAR - Ahmad Sirad; Basyarudin Basyarudin (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The issue of overcrowding in correctional facilities (prisons) has become a major concern within the criminal justice system in Indonesia, including at the Class I Correctional Facility in Makassar. One approach that can help address this issue is the implementation of restorative justice, which emphasizes conflict resolution through dialogue between the offender, the victim, and the community, rather than relying solely on imprisonment. This study aims to analyze the role of restorative justice in reducing overcrowding at the Class I Correctional Facility in Makassar by identifying the implementation of this policy and the factors that affect its success. The research method used is a qualitative approach with a descriptive design, involving data collection through literature review and documentation related to the implementation of restorative justice at the facility. The results show that although restorative justice has significant potential to reduce the number of inmates in correctional facilities, its implementation is still hindered by several factors, such as limited resources, lack of public understanding, and coordination challenges between agencies. Based on these findings, this study recommends the need for enhanced training for law enforcement personnel and strengthening policies that support the application of restorative justice as an effective alternative to punishment. Thus, the implementation of restorative justice can make a significant contribution to reducing overcrowding at the Class I Correctional Facility in Makassar and create a more humane and sustainable criminal justice system.